2021
DOI: 10.1111/joim.13334
|View full text |Cite
|
Sign up to set email alerts
|

Clinical benefits of TNF‐α inhibitors in Chinese adult patients with NLRP3‐associated autoinflammatory disease

Abstract: Background Nucleotide‐binding oligomerization domain‐like receptor family, pyrin domain containing 3 (NLRP3)‐associated autoinflammatory disease (NLRP3‐AID) is a rare, heterogeneous disease entity associated with mutations in NLRP3. Biologic therapy for NLRP3‐AID yields diverse results. Objectives We aimed to evaluate the clinical features and outcomes of Chinese adult patients with NLRP3‐AID who were treated with tumour necrosis factor (TNF)‐α inhibitors. Methods Five patients with NLRP3‐AID were diagnosed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“… Q705K did not describe other symptoms except for neurological involvement ( 29 ). K129R, Q703K, V70M, P38S, and D29V did not describe neurological involvement, so they were excluded from the denominator ( 30 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Q705K did not describe other symptoms except for neurological involvement ( 29 ). K129R, Q703K, V70M, P38S, and D29V did not describe neurological involvement, so they were excluded from the denominator ( 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…The reported CAPS were less than 100 until now in China (26,27,(29)(30)(31)(32)(33)(34)(35). The number of reported cases is very limited compared with the large number of potential CAPS patients in China.…”
Section: Characteristics For Novel Mutations and Comparison With Prev...mentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported increased NFkB activation and defective autophagy as potential pathogenic mechanisms (16)(17)(18). In our previous study, we observed a good response to TNF inhibitors in CAPS patients (19). Whether there are other pathways involved in the pathogenesis of SAIDs, and what the underlying mechanisms are in response to TNF blocking therapy, remain to be elucidated.…”
Section: Introductionmentioning
confidence: 77%
“…Some studies have reported increased NFκB activation and defective autophagy as potential pathogenic mechanisms (Bachetti et al, 2013; Hua et al, 2018; Nedjai et al, 2008). In our previous study, we observed a good response to TNFα inhibitors in CAPS patients (Wu et al, 2021). Whether there are other pathways involved in the pathogenesis of SAIDs, and what the underlying mechanisms are in response to TNFα blocking therapy, remain to be elucidated.…”
Section: Introductionmentioning
confidence: 84%